Quantitative market analysis of the European Climate Services sector – The application of the kMatrix big data market analytical tool to provide robust market intelligence - Steve Howard; Sarah Howard; Simon Howard (Climate Services, 2020)
Although activities within the Climate Services sector have been offered to public and private sector markets for a long time, the concept of “Climate Services” as a distinct sector is relatively new. Traditionally, these services have been considered an extension of Weather Services, but as the awareness of the Climate Services sector has spread, so has the need for in-depth, reliable and quantifiable market intelligence. The kMatrix big data analytical tool is a unique research methodology, providing market intelligence for “hard to measure” markets. The kMatrix method was applied to the Climate Services sector to define, measure and forecast the current and potential future market volume of the sector. The MARCO definition of Climate Services was developed by using an existing kMatrix Weather & Climate Services dataset, which was then scrutinized by the MARCO partners and a distinct and extended Climate Services taxonomy developed. Market intelligence is provided by country, industry, platform and service and includes value of sales (€m), import and export data, number of transactions, market growth rates, benchmarks of innovation and supplier and purchaser transactional data. The data has been mapped to NACE codes and NUTS 2 regions. The work provides a geographic baseline for Climate Services and allows for country and regional analysis. It provides a common definition of the sector and quantifies the market for those involved in the provision of climate services, policy makers and others, to have access to reliable market intelligence to monitor and assist in decision making at all levels. Keywords: Market data, Market measurement, Transactional data, Big data, Monitoring